Pass-through of commodity price to Mongolian stock price: Symmetric or asymmetric?. (March 2021) - Badamvaanchig, Mungunzul; Islam, Moinul; Kakinaka, Makoto
Abstract: Mongolia is a natural resource-rich country, so that its stock market is highly dependent on price fluctuations of commodities, particularly copper and coal. One crucial problem is that the responses of the stock market performance to a shock of the commodity price can be nonlinear or asymmetric. This study addresses such asymmetric linkages by applying nonlinear autoregressive distributed lags (NARDL) models during the period from January 2007 to December 2018. The results show clear evidence of asymmetric long-run relationships between stock price and the commodity price, supporting that different behaviors of stock price in response to positive and negative shocks on the commodity price. Specifically, our analysis presents a positive relationship between copper price and stock price in the case of a positive shock on copper price, but no clear relationship in the case of a negative shock on copper price. The results also reveal a positive relationship between coal price and stock price in the case of a negative shock on coal price, but no clear relationship in the case of a positive shock on coal price. The Mongolian stock market is favorably sensitive to an increase in copper price but vulnerable to a decline in coal price. Possible explanations behind the results are also discussed. Highlights: Mongolian stock market is highly dependent on price fluctuations of copper and coal. We identify asymmetric long-run relationships between stock price and the commodity price. We notice a positive relationship between copper price and stock price in the case of a positive shock on copper price. We show a positive relationship between coal price and stock price in the case of a negative shock on coal price. The Mongolian stock market is favorably sensitive to an increase in copper price but vulnerable to a decline in coal price.